Prevalence of Musculoskeletal Disorders in Kintamani Dog - Bianti Purwanto, Deborah; Werdi Susari, Ni Nyoman; Puja, I Ketut (Veterinary Science and Medicine Journal; Vol 3 No 2 (2015), 2015)
Kintamani dog is the emerging breed of dog from Bali Indonesia. The study was conducted to determinethe prevalence of the type of musculoskeletal disorders in Kintamani dogs based on the data presented atmany veterinary clinics in Bali during a period of five years from January 2009 to December 2013. A totalof 475 samples was obtained and their variations in prevalence were analyzed on the basis of age and sex.The prevalence of musculoskeletal disorders in Kintamani dogs included accidental wound (3.2%), arthritis(1.3%), lameness (0.8%), nail injury (0.2%), and hip dysplasia (0.0%). Based on this study we concludedthat Kintamani dog could be expected not susceptible to musculoskeletal disorders.
Keywords: Kintamani dogs; prevalence; musculoskeletal disorders